Prosthodontic Management of Oroantral Fistula: A Case Report - Aalam, MS; Pathak, B; Khanal, B; Devkota, D (Journal of Nepalese Prosthodontic Society, 2024)
An oroantral communication is an un-natural communication between the oral cavity and maxillary sinus. Most common cause of oroantral communication is extraction of upper molars and premolar teeth. Oroantral fistula develops when oroantral communication fails to heal spontaneously and remains patent and gets epithelized. The ideal treatment is immediate surgical repair using various surgical techniques. This article presents prosthodontic management of oroantral fistula using obturator after failure of surgical repair.